Improving Hand Function of Severely Impaired Chronic Hemiparetic Stroke Individuals Using Task-Specific Training With the ReIn-Hand System: A Case Series - Camona, Carolina; Wilkins, Kevin B.; Drogos, Justin; Sullivan, Jane E.; Dewald, Julius P. A.; Yao, Jun (Frontiers in Neurology, 2018)
Purpose: In this study, we explored whether improved hand function is possible in poststroke chronic hemiparetic individuals with severe upper limb motor impairments when they participate in device-aided task-specific practice. Subjects: Eight participants suffering from chronic stroke (>1-year poststroke, mean: 11.2 years) with severely impaired upper extremity movement (Upper Extremity Subscale of the Fugl-Meyer Motor Assessment (UEFMA) score between 10 and 24) participated in this study. Methods: Subjects were recruited to participate in a 20-session intervention (3 sessions/7 weeks). During each session, participants performed 20–30 trials of reaching, grasping, retrieving, and releasing a jar with the assistance of a novel electromyography-driven functional electrical stimulation (EMG-FES) system. This EMG-FES system allows for Reliable and Intuitive use of the Hand (called ReIn-Hand device) during multi-joint arm movements. Pre-, post-, and 3-month follow-up outcome assessments included the UEFMA, Cherokee McMaster Stroke Assessment, grip dynamometry, Box and Blocks Test (BBT), goniometric assessment of active and passive ranges of motion (ROMs) of the wrist and the metacarpophalangeal flexion and extension (II, V fingers), Nottingham Sensory Assessment–Stereognosis portion (NSA), and Cutaneous Sensory Touch Threshold Assessment. Results: A nonparametric Friedman test of differences found significant changes in the BBT scores (χ2 = 10.38, p < 0.05), the passive and active ROMs (χ2 = 11.31, p < 0.05 and χ2 = 12.45, p < 0.01, respectively), and the NSA scores (χ2 = 6.42, p < 0.05) following a multi-session intervention using the ReIn-Hand device. Conclusions: These results suggest that using the ReIn-Hand device during reaching and grasping activities may contribute to improvements in gross motor function and sensation (stereognosis) in individuals with chronic severe UE motor impairment following stroke.